In Vitro and In Vivo Antimicrobial Activity of the Novel Peptide OMN6 against Multidrug-Resistant Acinetobacter baumannii - Janna Michaeli; Shira Mandel; Shelly Maximov; Jonathan Zazoun; Paola Savoia; Nimmi Kothari; Thomas Valmont; Livia Ferrari; Leonard R. Duncan; Stephen Hawser; Moshe Cohen-Kutner; Niv Bachnoff (MDPI AG, 2022)
The rapid worldwide spread of antimicrobial resistance highlights the significant need for the development of innovative treatments to fight multidrug-resistant bacteria. This study describes the potent antimicrobial activity of the novel peptide OMN6 against a wide array of drug-resistant Acinetobacter baumannii clinical isolates. OMN6 prevented the growth of all tested isolates, regardless of any pre-existing resistance mechanisms. Moreover, in vitro serial-passaging studies demonstrated that no resistance developed against OMN6. Importantly, OMN6 was highly efficacious in treating animal models of lung and blood infections caused by multidrug-resistant A. baumannii. Taken together, these results point to OMN6 as a novel antimicrobial agent with the potential to treat life-threatening infections caused by multidrug-resistant A. baumannii avoiding resistance.